1992
DOI: 10.1128/iai.60.3.1114-1121.1992
|View full text |Cite
|
Sign up to set email alerts
|

Opsonin-independent phagocytosis of group B streptococci: role of complement receptor type three

Abstract: The role of complement receptor type 3 (CR3) in nonopsonic recognition of group B streptococci (GBS) by macrophages was investigated. Monoclonal anti-CR3 (anti-Mac-1) inhibited phagocytosis of GBS strains by as much as 50% in serum-free cultures of both mouse peritoneal macrophages and the macrophage cell line PU5-1.8. GBS uptake was unaffected by the presence of anti-C3 or salicylhydroxamate, an inhibitor of the covalent binding reaction of C3. Soluble antibodies to LFA-1 or to the common beta-chain (CD18) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…These results may have direct relevance to the observation that OKM1 was shown to inhibit the binding of opsonized M. tuberculosis to MDMs to a greater extent than that shown by Leu-15 (44 to 50% versus 34 to 39%, respectively) (44), which strongly suggests that a significant component of the binding of M. tuberculosis to CR3 is opsonin independent, irrespective of the presence or absence of C3 on the bacterial surface. This interpretation par-allels the conclusions reached for the opsonin independence of the binding of zymosan particles to neutrophil CR3 (40) or group B streptococci to CR3 on neutrophils and monocytes (1), where in both cases binding was not inhibited by a large excess of Fab anti-C3.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results may have direct relevance to the observation that OKM1 was shown to inhibit the binding of opsonized M. tuberculosis to MDMs to a greater extent than that shown by Leu-15 (44 to 50% versus 34 to 39%, respectively) (44), which strongly suggests that a significant component of the binding of M. tuberculosis to CR3 is opsonin independent, irrespective of the presence or absence of C3 on the bacterial surface. This interpretation par-allels the conclusions reached for the opsonin independence of the binding of zymosan particles to neutrophil CR3 (40) or group B streptococci to CR3 on neutrophils and monocytes (1), where in both cases binding was not inhibited by a large excess of Fab anti-C3.…”
Section: Discussionsupporting
confidence: 81%
“…Stokes et al (48) observed considerable variations among different M. tuberculosis complex strains and other mycobacterial species in the extent of nonopsonic binding to murine macrophages. Similarly, Antal et al (1) noted that the C3-independent binding of another gram-positive bacterium, group B streptococcus, to CR3 is likely strain dependent. The reported studies on M. tuberculosis binding to monocyte/macrophage complement receptors were performed predominantly with the Erdman strain (43,44) or the H37Ra strain (20) grown in rich medium (7H9 broth).…”
Section: Discussionmentioning
confidence: 96%
“…In vitro and in vivo virulence assays with unencapsulated or asialo mutants support the hypothesis that type III capsule serves as a virulence factor [11,12]. Other studies have shown that well encapsulated GBS are able to enter and persist in macrophages by evading intracellular opsonin-mediated antibacterial activities [13,14]. The role of the polysaccharidic capsule in the opsoninindependent uptake is so far unknown.…”
Section: Introductionmentioning
confidence: 59%
“…Complement-dependent phagocytosis is mediated by the CR3 (CD11b/CD18, ␣ M ␤ 2 ), which belongs to the ␤ 2 -integrin family, and it was shown that CD11b is critical for the recognition of C3bi [38], the activation product of C3. Additionally, CR3 can recognize microbes, e.g., type B streptococci, by interacting directly with molecules on their surface [39]. As SFKs are downstream of the CR3 pathway [40], we investigated the effect of CR3 (CD11b Ϫ/Ϫ ) deficiency in pneumoccocal meningitis to explore the functional differences between the two strains.…”
Section: Discussionmentioning
confidence: 99%